A smoothly bounded domain in a complex surface with a compact quotient - Cheung, Wing Sum; Fu, Siqi; Krantz, Steven G.; Wong, Bun (Mathematica Scandinavica, 2002)
We study the classification of smoothly bounded domains in complex manifolds that cover compact sets. We prove that a smoothly bounded domain in a hyperbolic complex surface that covers a compact set is either biholomorphic to the ball or covered by the bidisc.